Comparison of the Efficacy and Safety of Single-Session OK-432 and Multiple-Session 99% Ethanol Sclerotherapy for Symptomatic Simple Hepatic Cysts - Mo, Zhiqiang; Yang, Fangfang; Lv, Ling; He, Jian; Gou, Qin; Chen, Xiaoming; Zhuang, Wenhang; Mai, Qicong (Frontiers in Medicine, 2022)
Purpose: This retrospective study aimed to compare the efficacy and safety of single-session OK-432 and multiple-session 99% ethanol sclerotherapy for symptomatic simple hepatic cysts. Methods: We reviewed patients who received aspiration sclerotherapy with OK-432 (group A) or 99% ethanol (group B) for symptomatic simple hepatic cysts at Guangdong Provincial People’s Hospital from January 2013 to November 2019. Results: We included 42 patients in group A and 39 patients in group B. No significant difference was found in the mean volume of hepatic cysts between the two groups. The overall success rates were 92.9% (39 of 42 patients) in group A and 79.5% (31 39 patients) in group B (P=0.08). The treatment success for cyst volumes <200 ml, 200 ml-500 ml, and >500 ml were 100%, 93.3%, and 88.2% in group A, and 100%, 84.6%, and 57.1% in group B, respectively. The symptomatic relief rate in group A was higher than that in group B for cysts ≥500 ml (P=0.049) and for cysts <500 ml. For treatment-related complications, the incidence of pain at the injection site in group A was lower than that in group B. Conclusion: Single-session OK-432 sclerotherapy was safer and more effective than multiple-session 99% ethanol sclerotherapy for treating large cysts, although both treatments had similar effects on small cysts.